Role of carglumic acid in the long-term management of propionic and methylmalonic acidurias - Sufin Yap; Serena Gasperini; Shirou Matsumoto; François Feillet (Orphanet Journal of Rare Diseases)
Abstract Propionic aciduria (PA) and methylmalonic aciduria (MMA) are rare inherited disorders caused by defects in the propionate metabolic pathway. PA due to propionyl coenzyme A carboxylase deficiency results in accumulation of propionic acid, while in MMA, deficiency in methylmalonyl coenzyme A mutase leads to accumulation of methylmalonic acid. Hyperammonemia is related to a secondary deficiency of N-acetylglutamate (NAG), the activator of carbamoyl phosphate synthetase 1, which is an irreversible rate-limiting enzyme in the urea cycle. Carglumic acid (CGA) is a synthetic structural analog of human NAG and is approved for the treatment of patients with hyperammonemia due to PA or MMA. CGA is well tolerated and its use in normalizing ammonia levels during acute hyperammonemic episodes in patients with PA and MMA is well established. This expert opinion analyzed clinical evidence for CGA and discussed its place, along with other management strategies, in the long-term management of PA or MMA. A literature search of PubMed was undertaken to identify publications related to the chronic use of CGA, transplantation, dietary management, ammonia scavengers, and gene therapy for treatment of patients with PA or MMA. The authors selected the most relevant studies for inclusion. Four clinical studies, one single center case series, and three case reports show that CGA is safe and effective in the chronic treatment of PA and MMA. In particular, the addition of CGA is associated with a reduction in hyperammonemic decompensation episodes and admission to hospital, compared with conventional dietary treatment alone. Current treatment guidelines and recommendations include the use of CGA mainly in acute decompensation, however, lag in considering the benefits of long-term CGA treatment on clinical and biochemical outcomes in patients with PA or MMA. CGA is safe and effective in the chronic treatment of PA and MMA and may help to resolve some of the issues associated with other strategies used to treat these disorders. Thus, CGA appears to have potential for the chronic management of patients with PA and MMA and should be recommended for inclusion in the chronic treatment of these disorders.